Epidemiological Features and Clinical Manifestations of Cutaneous Leishmaniasis: An Emerging Health Risk in Hambantota, Sri Lanka (Bangladesh Journal of Zoology, 2023)
Cutaneous leishmaniasis (CL) is an established disease in Sri Lanka. Present study was designed to investigate the epidemiological features, clinical manifestations and the relationship between CL cases and rainfall in Hambantota district, Sri Lanka from March, 2014 to December, 2015. CL suspected patients who presented to Tangalle and Hambantota hospitals during this period were included in the study. After conducting a clinical examination, a descriptive study was carried out using a questionnaire. Slit-skin smears were taken, stained with Giemsa and examined under a light microscope to identify Leishmania amastigotes. Results showed that the highest CL cases were reported from Tangalle District Secretory Division (DSD) out of 12 DSDs in Hambantota district (P50 years old. Males were more infected than females. Higher number of CL patients were students (χ2 (10) = 6.41, P=0.781). Most of the patients had single lesion on arms, legs and faces/cheeks. Size of the most lesions was >2mm -